THE PARADIGM SHIFT OF THE LGBTQ COMMUNITY IN INDIA: A STUDY CONCERNING THE FUTURE OF SAME-SEX MARRIAGE AND CONJUGAL RIGHTS - Simrat; Banerjee Mukherjee, Sulakshana (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The LGBTQ community has been fighting for decades, and various movements are taking place around the world. While there have been notable advancements in LGBTQ rights activism in India in recent years, obstacles still exist on both a social and legal level. Although the government must make sure that these rulings are broadly accepted by society, the courts have been crucial in rendering just and equitable verdicts. Unfortunately, neither the federal government nor the state governments have taken concrete steps to support LGBTQ people, and social acceptance is still elusive. LGBTQ people have fought and won lots of small battles in recent years, but their major concern is about marital status. Same-sex marriage is still illegal in India, and homosexuality was decriminalized there in 2018. Notably, same-sex couples now have rights comparable to those of married individuals, according to a historic Supreme Court ruling from August 2022. The Supreme Court has begun considering several petitions asking for same-sex marriage to be recognized. Advocates for LGBTQ people and same-sex couples hope for the best, but government authorities and religious organizations are adamantly against them. With a significant LGBTQ community of almost 10 million people in the nation, this conversation is crucial. To ensure full acceptance and equitable treatment for LGBTQ people within the framework of traditional Indian culture, the courts and legislature must set the direction for LGBTQ rights in India. They must also determine what legislative and social changes are necessary.